Predictors for Antipsychotic Dosage Change in the First Year of Treatment in Schizophrenia Spectrum and Bipolar Disorders - Ringen, Petter Andreas; Reponen, Elina Johanna; Vedal, Trude Seselie Jahr; Andreassen, Ola A.; Steen, Nils Eiel; Melle, Ingrid (Frontiers in Psychiatry, 2019)
Background Use of antipsychotic medication is central in the treatment of psychotic disorders. However, there is limited knowledge about prescription practice of antipsychotics in the critical early phase of these disorders. Clinical guidelines recommend low dosages, but no discontinuation of antipsychotic medication during the first year of treatment in first episode patients. The main aim of this study was to identify clinical predictors for dosage change or discontinuation of antipsychotics during this period Methods A total of 426 antipsychotic-using patients with schizophrenia spectrum or bipolar disorder, including both a first treatment sample and a sample of patients with previous treated episodes (“multi episode” sample) from the same diagnostic groups, underwent thorough clinical and sociodemographic assessment at study baseline and after one year. Prescribed dosage levels at baseline and follow-up and change in dosage or discontinuation of antipsychotics from baseline to follow-up were compared between groups, controlling for possible confounders. Results We found higher levels of antipsychotic use in the schizophrenia group than in the bipolar group both at baseline and follow-up, but with no differences between first-treatment and multi-episode groups at baseline. We found reduced dosages over the first year in the two first treatment groups across diagnoses, but not in multi-episode groups. Weight increase predicted dosage reduction in the schizophrenia group, while the level of psychotic symptoms at baseline predicted dosage reduction in the bipolar group. Conclusion Our findings show differences in prescribed dosages and discontinuation of antipsychotics across diagnostic groups, however with a trans-diagnostic reduction of prescribed dosages over the first year in treatment. There were different predictors for reducing dosages and for discontinuing antipsychotic medication over the first year in treatment.